2019
DOI: 10.3390/bs9120147
|View full text |Cite
|
Sign up to set email alerts
|

Digital Storytelling in Language Education

Abstract: Modern technology provides lots of opportunities in order to connect classrooms with the world. Technology provides a greater and better source of information, yet solutions are needed to be mediated through the appropriate remedy. The emergence of new technology and digital resources during the past few decades has significantly influenced the learning environment and educational prospects. However, one of the challenges of practitioners and researchers is preparing learners with the required skills for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…It improves the quality of education (Edyo, 2019) Using digital storytelling in classroom promotes creativity. It allows students to learn from real life situations (Moradi & Chen, 2019). It plays a major role in promoting religious values and principles among students (Abdulhameed, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…It improves the quality of education (Edyo, 2019) Using digital storytelling in classroom promotes creativity. It allows students to learn from real life situations (Moradi & Chen, 2019). It plays a major role in promoting religious values and principles among students (Abdulhameed, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For classifying the means, the researcher used the criteria that are shown in the third table below: Table : (2 Edyo (2019), Robin (2008), Smeda et al (2014), Sadik (2008), Abed Al-Mo'men (2018), Moradi & Chen (2019), Abdollahpour & Asadzadeh (2012), Maureen et al (2018), Yang andWu (2012), Fokides (2016). and Thang et al (2014) The researcher concluded that primary school students in UAE show positive attitudes towards using the digital storytelling method by teachers in classroom, because the overall mean is 4.05.…”
Section: Analysis Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…With appropriate technological tools such as editing software, learners empower themselves to be proficient in it as well as improving their knowledge acquisition, as a result, they are able to achieve the learning outcome which is to produce a creative and authentic DST (Sadik, 2008). DST represents an innovative approach in the ever-changing education landscape which helps to improve learning in terms of subject matter and acquisition of soft skills such as critical thinking, digital literacy and motivation (Moradi & Chen, 2019).…”
Section: Research Question 1: How Does Digital Storytelling Help To Improve the Learners' Comprehension Of A Literary Text?mentioning
confidence: 99%
“…Today, the duration of these narrations has been reduced further to a maximum of two minutes [2]. These videos include moving images, photographs, titles and effects such as transitions, often accompanied by the author's narrative voice or a background soundtrack [3]. These narratives are not implied to be works of art; in the sense of sophisticated technology, they are not glossy and commercial products but are somewhat distorted and imperfect from a formal and language point of view [4].…”
Section: Introductionmentioning
confidence: 99%